Development of control algorithms for modern inverters or converters of energy storage systems with functions of virtual synchronous machines - Skrypnyk, Rostyslav (National Technical University "Kharkiv Polytechnic Institute", 2024)
The ESCRI-SA project represents Australia's first large-scale Battery Energy Storage System (BESS), with the Dalrymple BESS featuring an innovative energy storage system capacity of 30 MW and 8 MWh (BESS). This system operates as a virtual synchronous generator with grid-forming capability. The introduction of such equipment into operation confirms that energy storage plays a crucial role in the energy system, both currently and in the future, where the growth of various types of renewable energy sources will continue.
Keywords: renewable energy sources; primary frequency response; inertia; inverters; power systems; mathematical modeling; computer models